2007
DOI: 10.1055/s-0039-1698329
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ABO Blood Types on Periodontal Status

Abstract: ObjectivesThe purpose of the present study was to determine whether there was a relationship between periodontal diseases and ABO blood groups.MethodsThis epidemiological study was carried out on 1351 subjects who were randomly selected from individuals referred to the Faculty of Dentistry clinics for periodontal treatment or for other reasons regarding dental health. The study based on periodontal condition, blood group, and medical history. The subjects were divided into three groups as those with gingivitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
46
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 11 publications
10
46
2
Order By: Relevance
“…The subjects from age of 25 years to 75 years who were diagnosed as chronic periodontitis patients were included in the study having been informed about the purpose and method of the study. This age group range was in accordance with the previous studies conducted by Demir T et al, 26 Mortazavi H et al 25 and Aravind T et al 23 It was observed that maximum males among north Indian population group were having B positive blood group especially in age groups of 36-45, 46-55 and 56-65 years which was followed by O positive blood group. These results were in the line with studies conducted on north Indian population by Gautam A et al 27 and Kokane NB et al 17 It was observed that in present study maximum males in south Indian population with chronic periodontitis among age groups of 36-45 and 45-55 years were having B positive blood group which was followed by O positive blood group in same age groups.…”
Section: Discussionsupporting
confidence: 90%
“…The subjects from age of 25 years to 75 years who were diagnosed as chronic periodontitis patients were included in the study having been informed about the purpose and method of the study. This age group range was in accordance with the previous studies conducted by Demir T et al, 26 Mortazavi H et al 25 and Aravind T et al 23 It was observed that maximum males among north Indian population group were having B positive blood group especially in age groups of 36-45, 46-55 and 56-65 years which was followed by O positive blood group. These results were in the line with studies conducted on north Indian population by Gautam A et al 27 and Kokane NB et al 17 It was observed that in present study maximum males in south Indian population with chronic periodontitis among age groups of 36-45 and 45-55 years were having B positive blood group which was followed by O positive blood group in same age groups.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that the distribution of ABO blood group alleles varies between different populations (22). Our results match with the ones from a Mexican population (18), but are very different from a Turkish population, where the A group is predominant (19) or Indians, where the B group prevails.…”
Section: Discussionsupporting
confidence: 80%
“…There is variety in blood typing according to 6 races. Group B in Chinese and Indians, group A is widely distributed in Eskimos, the group O in A m e r i c a n a n d C a n a d i a n I n d i a n s a n d 7…”
Section: Introductionmentioning
confidence: 99%